2019
DOI: 10.1109/access.2019.2936620
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Optimize Web Interactions on Heterogeneous Mobile Systems

Abstract: The web has become a ubiquitous application development platform for mobile systems. Yet, web access on mobile devices remains an energy-hungry activity. Prior work in the field mainly focuses on the initial page loading stage, but fails to exploit the opportunities for energy-efficiency optimization while the user is interacting with a loaded page. This paper presents a novel approach for performing energy optimization for interactive mobile web browsing. At the heart of our approach is a set of machine learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 46 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…Existing works largely optimize the initial page loading phase, but as we demonstrate below, interactions have higher energy drain and thus more potential for savings. The few works [6], [11], [17] to address interactions assume a fixed response deadline for web content, but this runs the risk of degrading the overall user experience. By contrast, CAMEL minimizes energy consumption without compromising QoE, by offering "sufficiently good" performance.…”
Section: Background and Motivation Camel Reduces Energy Usage Durmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing works largely optimize the initial page loading phase, but as we demonstrate below, interactions have higher energy drain and thus more potential for savings. The few works [6], [11], [17] to address interactions assume a fixed response deadline for web content, but this runs the risk of degrading the overall user experience. By contrast, CAMEL minimizes energy consumption without compromising QoE, by offering "sufficiently good" performance.…”
Section: Background and Motivation Camel Reduces Energy Usage Durmentioning
confidence: 99%
“…• EBS: A regression-based method for adjusting the processor frequency to meet a fixed response deadline [6]; • Phase-aware: An event-phase-based power management strategy for mobile web browsing [17]; • ML-governor: A machine-learning-based CPU frequency governor for interactive web browsing [11]; • eBrowser: This strategy puts the browser process into sleep to drop some of the input user events [12]. All the above schemes require learning on the entire training dataset for each hardware architecture.…”
Section: B Competitive Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictive Modeling. Recent studies have shown that machine learning based predictive modeling is effective in code optimization [43], [44], performance predicting [45], [46], parallelism mapping [20], [47], [48], [49], [50], and task scheduling [51], [52], [53], [54], [55], [56]. Its great advantage is its ability to adapt to the ever-changing platforms as it has no prior assumption about their behavior.…”
Section: Domain-specific Optimizationsmentioning
confidence: 99%